A Modified Three Leg Watkins Johnson Bridge Type DC to DC Converter Simulation and Experimental Verification - Jothi Arulkumar Austin V.*; Ravi A.; Balasubramonian M. (Tehnički Vjesnik, 2022)
In this work, a novel, high boost, DC-to-DC converter topology is proposed and validated. The proposed topology is an extension of the existing two leg bridge type Watkins Johnson DC to DC converter. In the proposed system, an additional leg is included along with an additional inductor and an additional capacitor. The inclusion of the third leg to the existing, two-leg version of Watkins Johnson DC–to-DC bridge type converter helps to boost further the voltage gain. This paper presents the proposed topology and a detailed analysis of the topology using the circuit model in the MATLAB SIMULINK simulation environment. An experimental prototype was also developed to validate the proposed idea. The results obtained from the simulations and the experimental prototype are also presented herein. The studies were carried out with open loop configuration.